Exploring the Heterogeneous Effects of State Price Transparency Laws on Charge Prices, Negotiated Prices, and Operating Costs - Sebastian Linde; Ralph Siebert (Center for Economic Studies and ifo Institute (CESifo), 2021)
To limit the dramatic growth of U.S. health care expenditures, some states have mandated that medical providers publicly report their charge prices. Our study evaluates the heterogeneous effects of this price transparency policy. We use a comprehensive database that covers more than 2,000 hospitals nationwide from 1996 to 2017. We employ a flexible generalized synthetic control method that allows for heterogeneous treatment effects. We find that the price transparency policy not only reduced charge prices by 3.9% (which corresponds to savings of 1,164 per hospital stay) but also diminished negotiated prices by 15.9% and hospital costs by 4.7%. Our estimation results show that the effects on charge prices do not last as long as the impacts on negotiated prices and costs. We also find large heterogeneous responses across hospitals that depend on: (1) hospitals' past charge prices prior to adopting the price transparency law, that is, high-price hospitals reduce charge and negotiated prices, while low-price hospitals increase charges; (2) hospital characteristics such as ownership, case mix, and payer mix; and (3) hospital size and market competition. We also conduct counterfactuals to predict price changes of non-treated states and find large reductions in negotiated prices.
Keywords: C10; C33; I10; I11; 330; charge prices; difference-in-difference; heterogeneous treatment effects; hospitals; hospital costs; interactive fixed effects; negotiated prices; price transparency laws; synthetic controls